Research on the Construction of the "Five in One" Labor Education System in Applied Universities - Wang, Lu (Education Insights, 2025)
This study focuses on the construction of a labor education system in applied universities, deeply explores the problems existing in current labor education in applied universities, and innovatively proposes a five in one education system of "value guidance curriculum reform teacher optimization practice expansion evaluation reconstruction". Aiming to effectively enhance students' labor literacy and comprehensive abilities, it provides new ideas for the reform of labor education in applied universities. This study has important theoretical and practical significance for improving the training mode of applied talents and promoting the connotative development of higher education.